Neuroscience of clinical psychiatry : the pathophysiology of behavior and mental illness - Higgins, Edmund S. (Wolters Kluwer, Lippincott Williams & Wilkins, Health, 2013)
"Neuroscience of Clinical Psychiatry, Second Edition Fully revised and updated in its Second Edition, this handy and accessible reference provides a basic link between the science of the brain and the treatment of common mental health disorders. Ideal for the mental health clinician in training, the psychiatric resident preparing for Board exams, and the practicing clinician looking to keep pace with the latest advances in neuroscience, the book uses clear and direct language to enhance your understanding of basic neuroscientific concepts and the effects of brain chemistry on common behaviors and disorders. Updated content reflects the latest advances in the field, while straightforward discussions make complex material easy to understand and process. The book's concise presentation helps readers grasp, retain, and apply essential concepts. Abundant illustrations and tables support the text and provide vital information at a glance. End-of-chapter review questions reinforce key concepts and assist in Board preparation. Look inside and discover ... Updated content reflects the latest advances in the field. Straightforward discussions make complex material easy to understand and process. Concise presentation helps you grasp, retain, and apply essential concepts. Abundant illustrations and tables support the text and provide vital information at a glance. End-of-chapter review questions reinforce key concepts and assist in Board preparation. Pick up your copy today! "--